Influence of soil stabilizing materials on lead polluted soils using Jet Erosion Tests - Mutter, Ghazi M; Al-Madhhachi, Abdulsahib T; Rashed, Raghad R (International Journal of Integrated Engineering, 2017)
Solidification/stabilization treatment is usually used to stabilize site of contaminated land.Â Several common binding materials, such as cement, hydrated lime, and bitumen, were usually utilized as stabilizer materials for contaminated soil and tested by old techniques. Recent studies have been proposed that the high lead (Pb) concentration in soil causes an increase in soil erodibility, which is a major global environmental problem. An excess shear stress model is normally applied to measure soil erodibility based on two empirical soil parameters:Â critical shear stress (Ï„c) and erodibility coefficient (kd).Â Jet Erosion Test (JET) is one of recent technique to measure the soil erodibility parameters (Ï„c and kd) in the field as well as in the laboratory. The objective of this study was to investigate the influence of many building materials (cement, hydrated lime, and bitumen) on the stability of an artificially Pb-contaminated soil, using â€œminiâ€ JET device as a function of measuring soil erodibility parameters (Ï„c and kd). Hence, different percentages of three common Iraqi building materials (cement, hydrated lime, and bitumen) at different curing time were conducted to observe the effect of these materials on soil properties; such as Atterberg limits, dry density, optimum moisture content, and hardness as well as to soil erodibility parameters (Ï„c and kd). The results showed a reduction in kd value with increasing in the percentage of building materials and curing time, while Ï„c values were increased. The ideal mixing ratios of stabilizer materials showed that hardness degree increased by a ratio of 22% to 28.4%, while Atterberg limits either decreased or increased by a ratio of 5% to 28.5%. The results showed that all these materials can improve soil properties of Pb-contaminated soil and the cement was the best stabilizer. This study provides the benefit of using JET device in consume testing time and conserving energy, compared with other conventional techniques usually used for studying soil stabilization.Â